Assessment of Aflatoxin B1 Level in Chilli, Maize and Groundnut Samples from Kathmandu Valley - Gautam, Devaki Nandan; Bhatta, Rita; Bhandary, Megh Raj (Journal of Food Science and Technology Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Altogether 360 samples of Chilli, maize and groundnut (120 from each commodity) were collected from Kathmandu Valley in four different seasons from April 2007 to January 2008, for the determination of Aflatoxin B1 (AFB1). TLC Method was used for estimation of AFB1). Out of 360 samples, 88 (26 chilli, 30 maize and 32 groundnut) samples were found to be contaminated with AFB1 at the level of more than 10 µg/kg and average concentration of AFB1 in three commodities was found to be 50.8 µg/kg. Among the contaminated samples, chilli showed least amount of AFB1 i.e. 34.87 µg/kg on average; maize showed 50.17 µg/kg and ground nut showed the highest amount i.e.64.23 µg/kg of AFB1 contamination. Among the analyzed samples, 14 chilli, 18 maize and 24 ground nut were found to be contaminated with the AFB1 at more than 20 µg/kg (i.e. recommended maximum permissible level in Nepal) .Based on the seasonal variations, maximum number (26) and maximum amount (64.99 µg/kg) of contamination was found in April and January respectively among three commodities. Key words: AFB1; Contamination; Chilli; Maize; Groundnut; Kathmandu valley Journal of Food Science and Technology Nepal Vol. 4, September, 2008 Page: 57-60